Concept of Kafā’Ah in Marriage and Its Implementation among the Alawiyin Community in the Medan City, Indonesia - Hasanah Sadiqin; Syafruddin Syam; Imam Yazid (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
This research delves into the application of the Kafa'ah concept in Alawi marriages in Medan City. Kafa'ah, a regulated Islamic principle, emphasizes equality and suitability in selecting life partners, considering factors such as religion, lineage, wealth, and morality. Through literature review, interviews with key figures like Habib HA and Habib MA, and direct observation, the study examines how Alawis prioritize Kafa'ah nasab as the primary criterion for their offspring's marriages. The findings highlight the community's commitment to preserving the lineage of Prophet Muhammad, with most adhering strictly to Kafa'ah principles. However, a minority engages in marriages deviating from Kafa'ah, influenced by factors like awareness, territorial location, education, and economic demands. Data analysis exposes differing views between Alawis and mainstream fiqh scholars regarding Kafa'ah, aligning with the Hanbali school's mandate for its application. The study also uncovers a dilemma among sharifah, facing challenges in finding spouses within the sayyid community, necessitating consideration of marriages with non-sayyid individuals. This research contributes valuable insights into Alawi marriage dynamics in Medan City, shedding light on the implications of Kafa'ah nasab in preserving the lineage of Prophet Muhammad. Recommendations include maintaining community awareness and solidarity, with Rabithah Alawiyah involvement to address the struggles of sharifah seeking partners within the sayyid community.